Structural and functional studies of a 39,000-Mr immunodominant protein of vaccinia virus. - Maa, J S (1987)
Little is known about the nature of poxvirus proteins involved in the host immune response. Screening a lambda gt11 expression library of genomic rabbit poxvirus DNA with hyperimmune rabbit anti-vaccinia virus serum and selection of monospecific antibodies identified a highly antigenic viral protein of about 39,000 molecular weight (39K protein). The same-size protein of vaccinia virus was also identified with a monoclonal antibody (MAb B6) obtained from hybridomas generated after fusion of hyperimmunized mouse spleen cells with mouse myeloma cells. Structural analysis revealed that the 39K protein is an acidic polypeptide, that it can exist in two molecular forms because of intramolecular disulfide linkages, and that it is part of the virus core. This protein shares antigenic determinants with a cytoplasmic component(s) from uninfected cells. Functional studies revealed that the 39K protein is synthesized at late times postinfection and appears to be required for virus assembly. This protein is highly conserved in members of the Orthopoxvirus group, but in cowpox virus, a 41K virion protein was specifically recognized by antibodies that reacted against the vaccinia virus 39K protein. Significantly, during long-term passages of Friend erythroleukemia cells persistently infected with vaccinia virus, some virus mutants were found to increase or decrease by about 2 kilodaltons the size of the 39K protein. Mapping analysis localized sequences encoding the 39K protein in a rifampin-sensitive gene cluster between the two major core-associated viral polypeptides, 4a and 4b. The fact that the 39K core protein of vaccinia virus elicits strong humoral immune response, induces antibodies that react against a host component(s), and is subjected to genetic variability suggests that this protein has important biological functions.